Confirmation of the achievement of linear lesions using "activation vectors" based on omnipolar technology - Takigawa, Masateru; Goya, Masahiko; Ikenouchi, Takashi; Shimizu, Yuki; Amemiya, Miki; Kamata, Tatsuaki; Nishimura, Takuro; Tao, Susumu; Takahashi, Yoshihide; Miyazaki, Shinsuke; Sasano, Tetsuo (Heart rhythm, 2022)
Although differential pacing conventionally has been used to confirm the achievement of block across linear lesion sets, high-resolution mapping demonstrates that pseudo-block is observed in 20%-30% of cases. The purpose of this study was to examine the reliability and versatility of a method using "activation vectors" based on omnipolar technology to confirm the block line. Linear ablation was performed during pacing, with the HD Grid catheter (Abbott) placed beside the linear lesion opposite the pacing site. The endpoint of complete linear lesion was complete inversion of the activation vectors to the opposite direction. When inversion of the activation vectors was not observed after 10 minutes of radiofrequency (RF) application, high-resolution mapping was performed to assess whether complete block was achieved. In 33 patients, 24 cavotricuspid isthmus lines, 11 mitral isthmus (MI) lines, 16 posterior lines, and 2 intercaval lines were performed using this method. Of the total of 53 lines, 10 (18.9%) required intermediate evaluation of the block line with high-resolution mapping because of the absence of inversion of activation vectors despite 10 minutes of RF application, resulting in incomplete block with endocardial gaps or epicardial conductions. Additional RF applications finally achieved inversion in direction of activation vectors in the 10 lines. In total, the present method can diagnose achievement of complete block line with 100% accuracy, whereas conventional differential pacing misdiagnosed incomplete block with epicardial conduction in posterior lines in 3 cases and in MI lines in 2 cases. Confirmation of complete linear lesions using "activation vectors" based on omnipolar technology is a reliable and versatile method.